Lectures on martime studies - Suryanarayan, V.; Nambiar, E. K. G.; University of Calicut. Publication Division ([Calicut] : Publication Division, University of Calicut, 2005)
Contributed lectures delivered at the Chair for Martime Studies and Research, University of Calicut; with reference to Indian Ocean Region.
Keywords: Merchant marine -- Indian Ocean Region -- History; Indian Ocean Region -- Commerce -- History; India -- Commerce -- History